Refined method of blood collection in chickens using tonic immobility (Journal of Laboratory Animal Science, 2021)
The domestic fowl (Gallus gallus domesticus) is a popular commercial species and is much studied for meat and egg  production. Frequent studies on genetics, immunology, diagnostics and therapeutics are conducted in this species. For  all these studies frequent blood collection is required. In the present study, blood collection technique in domestic fowl  was standardized, wherein a single individual researcher can restrain the bird using the weak hand in the state of tonic  immobility and carry out blood collection using the dominant hand, thus precluding the need for additional manpower  which enhances the efficiency of collection especially for studies involving large number of birds without exposing them  to much stress and discomfort. This fulfils one of the important objectives of refining experimentation by reducing stress  on the birds.
Keywords: Blood collection; Chicken; Refinement; Tonic immobility